C1qtnf6 Expression as a Prognostic Biomarker and Therapeutic Target in Lung Adenocarcinoma: Implications for Immune Infiltration and Tumor Progression - Qincai Li; Hua Zhang; Hai Yun‐Liu; Peifeng Zheng; Xiaogang Xu (Cancer Reports, 2025)
ABSTRACT Background The incidence and mortality of lung cancer are increasing every year, making it the primary cause of cancer‐related fatalities globally. Upregulation of C1qtnf6 expression is observed in various human cancers. This study aimed to explore the function of C1qtnf6 in lung adenocarcinoma (LUAD) progression. Methods We used The Cancer Genome Atlas (TCGA) dataset to analyze data on lung cancer. The relationship between C1qtnf6 expression and treatment outcomes in patients with LUAD was evaluated using a Kaplan–Meier survival analysis. The receiver operating characteristic (ROC) curve was analyzed to ascertain the diagnostic value of C1qtnf6 in LUAD. Additionally, we performed a correlation analysis to investigate the association between the transcription of C1qtnf6 and inflammation in LUAD. To create LUAD cell lines with reduced C1qtnf6 expression, C1qtnf6 was knocked down, and several in vitro analyses were conducted to determine how C1qtnf6 knockdown affected the proliferation and apoptosis of LUAD cells. Furthermore, the relationship between C1qtnf6 and Interleukin‐10 (IL‐10) was verified. Using the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis and Gene Ontology (GO) studies, we further examined the impact of C1qtnf6 knockdown on the biological behavior of LUAD cells. Results TCGA dataset analysis revealed that C1qtnf6 expression was much higher in LUAD tissues than in the adjoining normal tissues. Correlation analysis revealed a relationship between C1qtnf6 expression and immune cell infiltration in LUAD. It has been demonstrated that C1qtnf6 expression is closely associated with the tumor immunological milieu, immune checkpoint blockade (ICB), and response to cisplatin treatment. In vitro tests revealed that C1qtnf6 knockdown reduced IL‐10 levels, accelerated apoptosis, and hindered the growth of LUAD cells, thus indicating a possible link between C1qtnf6 and inflammation. Conclusion Our results show that C1qtnf6 may be useful as a prognostic indicator for LUAD.